Development of Health Screening Information System for Elementary School Children at Dalam Kaum Sambas Public Health Center, Sambas Regency - West Kalimantan - Saherman Mohammad; Farid Agushybana; Mursid Raharjo (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2023)
Dalam Kaum Sambas Public Health Center is one of the public health centers that carry out the main activities of health improvement efforts in the form of promotive and preventive efforts, namely health screening for elementary school children, which are carried out manually, causing problems such as the length of recording, drawing conclusions based on examination results and recapitulation that are at risk of errors. This study aimed to develop an Information System for Primary School Children's Health Screening (SIPEKASDA) at Dalam Kaum Sambas Public Health Center. This research method is Research and Development (R&D) with system design using the Waterfall model and system evaluation with the EUCS End User Computing Satisfaction (EUCS) model. The design of the Information System in this study includes a Data Flow Diagram, Flowchart, Entity Relationship Diagram and User Interface, which produces an Information System with several menus, namely processing student data, parents, student class mapping, health checks and recapitulation of school-based health check results. The results obtained from SIPEKASDA include; the presentation of examination results data and recapitulation of examination results per school, village and sub-district. SIPEKASDA is a website-based information system that can be accessed anywhere and anytime. The quality of the Primary School Children's Health Screening Information System assessed from the evaluation of information systems using the End User Computing Satisfaction (EUCS) model is very good, which reaches 83.58%, so the information system can be relied on if you need data at any time. One of the principles of using information systems is timelines or the speed of information systems in responding to what is done by its users, presenting data promptly and up to date so that the use of information systems can increase. Problems in recording inspection results, data processing, data recapitulation, report making, and ease of accessing the system can be adequately resolved after the system is made.